Efektifitas Model Pembelajaran CCM-CCA Untuk Memfasilitasi Perubahan Konsep Gaya Pada Mahasiswa - Muh Makhrus; Wahono Widodo; Rudiana Agustini (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2018)
This study aims to examine the effectiveness of the CCM-CCA learning model that has been validated by physicist education through Focused Group Discussions (FGD) activities, and the validation results are valid in content and construct. The research design used follows the Education Research and Development method. The development of models starting from designing the model until implementing the model. Test the effectiveness of the model measured by the results of analysis of observational data and interview results on the occurrence of conceptual changes in students. Observation and interview data refers to the thought process experienced by students as a condition for conceptual change. The results of the study showed that students who were the subjects of the study experienced the four (4) thought processes that were the conditions for conceptual change. These results indicate that the CCM-CCA learning model is an effective learning model for facilitating the occurrence of student conceptual changes from wrong conceptions into scientific conceptions (physicist conception) about the concept of force